Social work in the global neoliberal context: solidarity and resistance from a radical perspective - Ioakimidis, Vasilios (Critical Proposals in Social Work, 2021)
Neoliberal capitalism has had a brutal impact in terms of increasing inequality throughout the world. This is closely related to the mental health problems growing among the general population, including social workers. In this article, I propose that there cannot be critical social work based genuinely on the search for social justice that does not emphasize human relationships; nor can there be social work based on human relationships that does not aspire to the promotion of social justice on a structural level. To argue around this position, discussions about neoliberalism and its impact on human relationships are addressed as a broad framework to think about social work today. The professional past is problematized and the current conditions in which the intervention of social workers takes place are analysed, which lead to reecting on the possibility of resistance. Based on the analysis of the acts of resistance of social workers in some European countries, a radical project of social work is proposed, which puts solidarity and care at the centre as a transforming impulse in our societies.